2000
DOI: 10.1034/j.1399-3054.2000.100310.x
|View full text |Cite
|
Sign up to set email alerts
|

Silverleaf whitefly stress impairs sugar export from cotton source leaves

Abstract: Silverleaf whitefly (SLW), Bemisia argentifolii Bellows and cose and fructose and decreased starch concentrations. Ex-Perring, is one of the most noxious pests of numerous field port rate was determined after 14 CO 2 pulse-labeling both by in situ monitoring of leaf radioactivity and by analyzing the and vegetable crops, causing billions of dollars worth of content and radioactivity of the major carbon metabolites. damage throughout the world. SLW is a phloem feeder Radioactive counting indicated a lower rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
3
12
1
Order By: Relevance
“…Crucially, these symptoms were not observed in resistant lines. Other experiments using 14 CO 2 labelling have confirmed that cotton leaves export less fixed carbon following infestation by the phloem‐feeding silverleaf whitefly and that soluble sugars accumulated in leaves, which further supports the hypothesis regarding the role of feedback inhibition of photosynthesis (Lin et al . 2000).…”
Section: Insect Herbivory Impacts Primary Metabolic Processessupporting
confidence: 79%
“…Crucially, these symptoms were not observed in resistant lines. Other experiments using 14 CO 2 labelling have confirmed that cotton leaves export less fixed carbon following infestation by the phloem‐feeding silverleaf whitefly and that soluble sugars accumulated in leaves, which further supports the hypothesis regarding the role of feedback inhibition of photosynthesis (Lin et al . 2000).…”
Section: Insect Herbivory Impacts Primary Metabolic Processessupporting
confidence: 79%
“…The latter has been shown for silverleaf whitefly infestations, whose feeding on leaves caused reduced photosynthate export from source tissues (Lin et al, 2000). Also, the flower should be an example sink tissue.…”
Section: Discussionmentioning
confidence: 86%
“…Petiole glucose levels were significantly correlated with densities of whitefly adults during the peak population size (Table 1). Whiteflies are known to impair photoassimilate export from leaves (Lin et al, 2000) which could lead to elevated glucose in leaf petioles. So, the correlation between glucose and whitefly numbers may be due to other factors.…”
Section: Discussionmentioning
confidence: 99%